PERBANDINGAN PENGARUH UKURAN PERUSAHAAN, OPINI AUDIT, PROFITABILITAS DAN REPUTASI KAP TERHADAP AUDIT DELAY (Studi Empiris pada Perbankan Konvensional dan Perbankan Syariah Tahun 2014-2016) - Laurencius Simatupang; Wirmie Eka Putra; Netty Herawaty (Jurnal Ilmiah Wahana Akuntansi, 2018)
This research aimed to determine empirically the comparison and effect ofcompany size, audit opinion, profitability and public accounting firm’s reputation to audit delay. The population in this research are conventional banking and syariah banking in the year of 2014-2016. The sampling technique used is purposive sampling with the number of samples is 45 companies. The analysis technique used in this research is panel data regression analysis and independent sample t-test. The results of this research conclude that: company size, audit opinion, profitability and public accounting firm’s reputation simultaneously effect to the audit delay on conventional banking and syariah banking. Company size and public accounting firm’s reputation partially effect to audit delay on conventional banking and syariah banking. Audit opinion and Profitability has no effect to audit delay on conventional banking and syariah banking. The variables audit delay, company size and profitability have significantly different rates between conventional banking and syariah banking, while the variables of audit opinion and public accounting firm’s reputation have no significant differences.